The Effect of Noise to Morphology of Rats (Mus Musculus) Spermatozoa (Universitas Negeri Semarang, 2020)
Infertility is a serious problem in health and social issue. Exposure to noise is one of the causes of physical and psychological stress that can activate central and peripheral responses in the endocrine system and autonomic nerves as a form of adaptation, so as to reduce the normal percentage of spermatozoa morphology. This study aimed to determine the effect of noise in rice milling on spermatozoa morphology. This study was conducted with laboratory experimental research methods with post-test only control group design. The rats were divided into 2 groups randomly, namely the control group with noise exposure +60 dB (KK) and the treatment group that received noise exposure Â± 90 dB (KP) in UD Berkah Tani Grinding Mill for 35 days. On the 36th day, the rats were terminated and spermatozoa were taken to giemsa staining, then observe under a microscope. The data normality were analyzed using Shapiro Wilk and homogeneity were tested using Levene test. The results showed that there were a significant in the spermatozoa morphology between the control and treatment group (p 0.05). It was indicate that there was a difference of noise exposure for 35 days.